2010
DOI: 10.1007/s00125-010-1677-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia-induced impairment of endothelium-dependent vasorelaxation in rat mesenteric arteries is mediated by intracellular methylglyoxal levels in a pathway dependent on oxidative stress

Abstract: Aims/hypothesisImpaired nitric oxide (NO)-dependent vasorelaxation plays a key role in the development of diabetic vascular complications. We investigated the effect of hyperglycaemia on impaired vasoreactivity and a putative role therein of the AGE precursor methylglyoxal.MethodsThe effects of high glucose and methylglyoxal on NO-dependent vasorelaxation in isolated rat mesenteric arteries from wild-type and transgenic glyoxalase (GLO)-I (also known as GLO1) rats, i.e. the enzyme detoxifying methylglyoxal, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
106
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(126 citation statements)
references
References 55 publications
12
106
1
Order By: Relevance
“…We previously addressed the reaction of the mesenteric endothelium to acetylcholine after short-time incubations with MGO or high glucose and in diabetic rats 12 weeks after STZ injection [14]. In the current study we confirmed these data in mesenteric arteries after 24 weeks of diabetes and extended our observations by specifically addressing which pathways are involved in the diabetes-induced impairment of acetylcholine-dependent relaxation.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We previously addressed the reaction of the mesenteric endothelium to acetylcholine after short-time incubations with MGO or high glucose and in diabetic rats 12 weeks after STZ injection [14]. In the current study we confirmed these data in mesenteric arteries after 24 weeks of diabetes and extended our observations by specifically addressing which pathways are involved in the diabetes-induced impairment of acetylcholine-dependent relaxation.…”
Section: Discussionsupporting
confidence: 84%
“…Measurement of vascular function, morphology and gene expression Vascular reactivity was measured as described earlier [14]. For further details see electronic supplementary materials [ESM] Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GLO1-overexpressing rats were crossed with wild-type (WT) Wistar rats to obtain enough GLO1 progeny for the experiment. The rats were obtained from the Nippon Seibutsu Zairyo Center (Saitama, Japan) and studies using these animals have been recently published [19,20]. All animal studies were carried out in accordance with the Guide for the Care and Use of Laboratory Animals of the National Institutes of Health.…”
Section: Methodsmentioning
confidence: 99%
“…This was accompanied by protection against high glucose-mediated dysfunction [17,18]. Overexpression of GLO1 in diabetic rats has been shown to be protective against AGE formation and oxidative stress in muscle [19], and also prevent abnormalities in endothelium-dependent vasorelaxation [20]. Likewise, regulation of GLO1 activity in cells can prevent diabetes-related cell dysfunction [21,22].…”
Section: Introductionmentioning
confidence: 98%